Detection of the Metabolic Relationship Between Primary Tumor in Breast Cancer According to Molecular Classification in Positron Emission Tomography; Retrospective Cohort Study - Ahmet Alyanak; Ferit Aslan (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2022)
The main objective of the study was to investigate whether the maximum SUV emission tomography values of Positron differ between luminal molecular properties. The second objective was to examine the relationship between positron emission tomography SUV max and ki67 in primary tumors and axillary lymphadenopathy. In the study between January 2018 and December 2020, 158 patients with stage 1-2-3 breast cancer admitted to the outpatient clinic of general surgery and medical oncology Yüksek htisas University Medicalpark Ankara were retrospectively evaluated. The results of the study considering the relationship between molecular properties and metabolic activity of primary tumors, found a significant relationship between grade (p<0.005), estrogen receptor (p:0.019), and progesterone receptor (p:0.045). More important differences were observed in the luminal type, especially between such as basal and luminal A (p: 0.021). A significant correlation was found in the Pearson correlation test, which was performed between the primary tumor and the SUV values for maxillary axillary lymphadenopathy (p < 0.001, correlation coefficient: 0.331). For Ki67, there was a significant, albeit low, correlation between the SUV max primary tumors (p: 0.026, correlation coefficient 0.179). Although there is a statistically positive trend between Ki67 and axillary SUV max, there is no significant difference (p: 0.06 correlation coefficient: 0.157) In conclusion, we found a significant relationship between max. positron emission tomography SUV, estrogen receptor, progesterone receptor, grade, ki67, and molecular subtypes such as basal and luminal A of the tumor. We found a correlation between the primary tumor and the metabolic activity of axillary lymphadenopathy. It will be meaningful to plan treatment and follow-up according to these results.